2018
DOI: 10.4172/2161-1122.1000524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silanization Conditions on Flexural Properties of Sic Fiber-Reinforced Resin

Abstract: Objective:The aim of this study was to evaluate the effects of silanization conditions on the mechanical properties of the SiC fiber-reinforced resin. Materials and Methods:A mixture of urethane dimethacrylate and Triethylene Glycol Dimethacrylate (TEGDMA), with camphorquinone and 2-(N,N-dimethylamino)ethyl methacrylate as the visible-light initiator, was prepared as a matrix resin. The SiC fiber containing 10 mass% oxygen was silanized by two methods, using experimental silane coupling agents containing 0.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…From the results of our previous study, it was suggested that silanization for SiC fibers improved the flexural strength and modulus of the SiC fiber-reinforced resin. Furthermore, the SiC fiber-reinforced resin prepared in the study showed greater flexural strength than the commercial composite resins used in dentistry [21].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…From the results of our previous study, it was suggested that silanization for SiC fibers improved the flexural strength and modulus of the SiC fiber-reinforced resin. Furthermore, the SiC fiber-reinforced resin prepared in the study showed greater flexural strength than the commercial composite resins used in dentistry [21].…”
Section: Introductionmentioning
confidence: 83%
“…Then, a short SiC fiber-reinforced resin was prepared. The fiber content was calculated based on the fiber content of the SiC continuous fiber-reinforced resin prepared in our previous study [21].…”
Section: Methodsmentioning
confidence: 99%